Organizational Behavioral Unit Kegiatan Mahasiswa: Studi Analisis Komitmen di Universitas Tidar - Agung Danur Pratama; Nabila Fatmasary; Arya Mangatur Manik; Tiara Novita Sari; Aisyah Nuraini Asmungi; Joko Tri Nugraha (PANDITA: Interdisciplinary Journal of Public Affairs, 2025)
This study aims to analyze the influence of organizational behavior factors, including leadership, motivation, and organizational climate, on the level of organizational commitment among Student Activity Unit (UKM) functionaries at Tidar University. A descriptive quantitative design was employed to provide an objective overview of students’ attachment to their organizations. The study involved a population of 855 functionaries from 19 active units, and 57 respondents were selected using proportionate stratified random sampling. Data were collected through a Likert-scale questionnaire and analyzed descriptively by calculating the mean, frequency distribution, and percentage across the three dimensions of organizational commitment proposed by Meyer and Allen: affective, continuance, and normative commitment. The findings show that the overall commitment level falls within the moderate-to-high category, with affective and normative commitment emerging as the most dominant dimensions. This indicates that emotional attachment, a sense of belonging, and moral responsibility serve as the main drivers encouraging students to remain active in their organizations. Rational considerations, such as long-term benefits, still play a role but remain less influential. These results reaffirm the relevance of the Three-Component Model of Organizational Commitment in the context of non-profit higher education organizations. Moreover, the study emphasizes the importance of participatory leadership, transparent communication, and a collaborative organizational culture as strategic foundations for strengthening loyalty, enhancing member motivation, and ensuring the sustainability of student organizations at Tidar University.